2020
DOI: 10.1002/adhm.202001205
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Feedback‐Controlled Photothermal/Photodynamic/Chemodynamic Combination Cancer Therapy Based on NaGdF4:Er,Yb@NaGdF4:Nd@Cu‐BIF Nanoassemblies

Abstract: The intelligent design of multifunctional nanoplatforms is critical for cancer therapy. Herein, NaGdF 4 :Er,Yb@NaGdF 4 :Nd@Cu(II) boron−imidazolate frameworks (denoted as CSNPs@Cu-BIF) nanoassemblies are designed and fabricated. Upon a single 808 nm laser irradiation, the nanoassemblies not only show the outstanding photothermal conversion capacity (= 41.7%) but also generate cytotoxic reactive oxygen species through an in situ Fenton-like reaction and fluorescence resonance energy transfer. Importantly, the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…There are some examples of using Cu‐containing nanomaterials for CDT‐involved multimodal therapy, [ 253–270 ] some of which are listed in Table 2. For example, Cu‐based CDT together with other therapies can enhance cancer immunotherapy.…”
Section: Applications Of Cdt In Anticancer and Antibacterial Therapiesmentioning
confidence: 99%
“…There are some examples of using Cu‐containing nanomaterials for CDT‐involved multimodal therapy, [ 253–270 ] some of which are listed in Table 2. For example, Cu‐based CDT together with other therapies can enhance cancer immunotherapy.…”
Section: Applications Of Cdt In Anticancer and Antibacterial Therapiesmentioning
confidence: 99%
“…The presence of the other dioxide, O 2 −• , was further verified using nitro‐blue tetrazolium (NBT), which exhibited a maximum absorption wavelength of 260 nm. [ 43 ] The absorbance of NBT was reduced in both X‐ray irradiation groups, especially in the SNP + X‐ray group, thus indicating high O 2 −• production by SNP under X‐ray irradiation (Figure 2e). These results indicated that SNP promoted the production of O 2 −• in radiotherapy because it has a strong X‐ray absorption capacity and reacts with the surrounding O 2 and water.…”
Section: Resultsmentioning
confidence: 99%
“…As emerging class of hybrid porous materials constructed from metal nodes and organic linkers, metal organic frameworks (MOFs) gain numerous attentions in recent years and widely applicated in catalysis, gas separation and conversion, chemical sensors, and biomedicine. , With the intrinsic characteristics of large surface areas and highly ordered porosities, MOFs exhibit potent capability of loading and releasing different therapeutic cargoes. Zeolitic imidazolate frameworks (ZIF-8) as a new porous material consist of zinc ions and 2-methylimidazole, which endow it with pH responsiveness, size controllable adjustment, and comparable compatibility. As an excellent drug carrier, cargoes can be easily encapsulated on the surface or center of ZIF-8 via multiple interactions such as electrostatic adsorption, coordination, and π–π stacking .…”
Section: Introductionmentioning
confidence: 99%